Immune cells in mesothelioma microenvironment simplistic marker of response to nivolumab plus ipilimumab?. (November 2022) - Disselhorst, Maria J.; Lubeck, Yoni; van der Noort, Vincent; Quispel-Janssen, Josine; Seignette, Iris M.; Sanders, Joyce; Peters, Dennis; Hooijberg, Erik; Baas, Paul
Highlights: Nivolumab plus ipilimumab is an effective treatment for malignant pleural mesothelioma. Biopsies before nivolumab plus ipilimumab treatment show a higher cell density of CD4+, CD8+, FoxP3+ and PD-1+ cells in responding patients. Biopsies during treatment with checkpoint inhibitors do not show a significant change when compared to baseline. Larger trials are needed with a more detailed analysis of mesothelioma tumor microenvironment. Abstract: Introduction: Malignant pleural mesothelioma (MPM) is a malignant disease of the pleura which recently can be treated with immune checkpoint inhibitors (ICI). To optimize this treatment, a better understanding of the tumor micro environment is needed. We investigated subgroups of immune cells in subsequent tumor biopsies of patients treated with ICI. Methods: Biopsies from MPM patients included in two clinical ICI trials (nivolumab alone and an ipilimumab/nivolumab combination) were examined. At baseline and after 6 weeks of treatment, pleural biopsies were taken to examine the tumor microenvironment (CD20+, CD4+, CD8+, FoxP3+ and PD-1+ ). Cell density was defined as the number of marker positive cells per mm 2 . Radiological responses were evaluated as partial response, stable disease or progressive disease according to modified RECIST criteria. Results: Thirty-four and 36 patients were included in the nivolumab and ipiliumumab/nivolumab trial respectively. In the nivolumab trial, no significant differences in cell densities were seen in baseline biopsies of patients with partial response versus progressive disease. In contrast, in the ipilimumab/nivolumab trial, a higher cell density of CD4+, CD8+, FoxP3+ and PD-1+ cells at baseline was significantly correlated with partial responses. On-treatment biopsies of both trials did not show significant changes when compared to baseline biopsies. Conclusion: Biopsies from patients responding to nivolumab plus ipilimumab treatment show a significant higher cell density of CD4+, CD8+, FoxP3+ and PD-1+ cells, without a change after 6 weeks of treatment. This observation is a first step in exploring the tumor microenvironment as predictor of response in ICI treatment in MPM.